The horse bone fragments from Mursa (Osijek) - Mihelić, Damir (2008)
During excavation of the archaeological site Mursa (Slavonija, Croatia)large quantity of horse bone fragments were found. Material was analyzed morphometricaly with identification of sex and age at death.